The effects of weight-bearing manipulations on gait and its underlying neural control mechanisms in toe walking children - Gwerder, Michelle; Visscher, Rosa M. S.; Spescha, Anusha; Hosseini Nasab, Seyyed H.; Kim, Yong K.; Zibold, Regine; Brunner, Reinald; Taylor, William R.; Viehweger, Elke; Singh, Navrag B. (Frontiers in Human Neuroscience, 2025)
IntroductionIn toe walking children, impaired maturation of neuromotor control often leads to persistent use of immature motor programs. Understanding the underlying etiology of toe walking in children with cerebral palsy (CP) and idiopathic toe walking (ITW) is crucial for advancing rehabilitation strategies. This study examined gait adaptations and H-reflex responses to varied weight-bearing conditions to determine whether children with ITW and CP exhibit distinct neuromotor control strategies compared to typically developing (TD) peers.MethodsEight children with CP (mean age 12.9 ± 2.1 years), eight with ITW (8.6 ± 1.9 years), and 19 TD children (10.0 ± 2.6 years) walked on a treadmill under three conditions: normal bodyweight, 30% bodyweight unloading, and 30% additional bodyweight. Linear mixed-effects models assessed spatiotemporal gait parameters, margin of stability, gait variability, and H-reflex responses.ResultsBodyweight unloading increased single-limb support time, while reducing double-limb support time and antero-posterior margin of stability across groups (p < 0.01). ITW children exhibited increased gait variability (p < 0.01) under bodyweight unloading, while CP children showed no change. H-reflex amplitudes decreased under bodyweight unloading in TD children, while CP children exhibited hyperreflexia (p < 0.05).DiscussionThe findings of this exploratory study suggest that toe walking is associated with distinct adaptive strategies in ITW and CP children to compensate for environmental challenges. In ITW, increased variability under bodyweight unloading may reflect exploratory motor control, whereas CP children relied on stiffening strategies, marked by reduced variability and hyperreflexia, indicating limited adaptability and less efficient gait patterns. These results imply that similar biomechanical constraints evoke divergent neuromotor adaptations in ITW and CP children.